Correction: Brandolini et al. The Evolution of Historic Agroforestry Landscape in the Northern Apennines (Italy) and Its Consequences for Slope Geomorphic Processes. Land 2023, 12, 1054 - Filippo Brandolini; Chiara Compostella; Manuela Pelfini; Sam Turner (Land, 2023)
In the original publication [...]